Inequalities in non-communicable diseases and effective responses (2013)
In most countries, people who have a low socioeconomic status and those who live in poor or marginalised communities have a higher risk of dying from non-communicable diseases (NCDs) than do more advantaged groups and communities. Smoking rates, blood pressure, and several other NCD risk factors are often higher in groups with low socioeconomic status than in those with high socioeconomic status; the social gradient also depends on the country's stage of economic development, cultural factors, and social and health policies. Social inequalities in risk factors account for more than half of inequalities in major NCDs, especially for cardiovascular diseases and lung cancer. People in low-income countries and those with low socioeconomic status also have worse access to health care for timely diagnosis and treatment of NCDs than do those in high-income countries or those with higher socioeconomic status.